What the Keynesian theory said about Portugal? - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
With this work it is intended to analyze the contributions of the Keynesian theory to the explanation of the regional evolution in Portugal. Considering the Keynesian models in different perspectives and taking into account the Verdoorn (1949) relationship it is did data and econometric analysis for the Portuguese economy in the period from 1995 to 1999. There are not many or none works based in the Keynesian theory and in the Verdoorn relationship for Portugal, namely at regional level. On the other hand the models based in this theory are regularly used to explain the regional economic growth in many countries. So, it is thought that analyze the economic Portuguese context with this theory is an important contribution to the economic theory and to the Portuguese understanding. As main conclusion it can be said that the Keynesian theory show for Portugal, in this period, regional and sectoral divergence.
Keywords: O18; C23; 330; Keynesian theory; Verdoorn law; Portuguese regions